RISK OF THE STABILITY INVESTMENT PROJECT - O. G. Kryukova; A. V. Evdokimova (Стратегические решения и риск-менеджмент)
The implementation of major investment projects in the gas sector is associated with different risks. To assess the impact of parameter changes on the financial result of the project is proposed to use the schedule "Spider", which allows you to clearly define how the results of the project NPV, depending on changes in values of the main input parameters of the project: selling price, capital expenditures, operating costs, production level. It determines the optimal structure of investment capital Monte Carlo.